Single‐layer and double‐layer zein–gum arabic nanoencapsulations: Preparation, structural characterization, thermal properties, and controlled release in the gastrointestinal tract. Issue 10 (13th September 2022) - Huang, Xueying; Ge, Xiaohan; Wang, Yi
Abstract: Encapsulation is one of the most convenient ways to increase the solubility of hydrophobic compounds and enhance the protection of sensitive compounds. The development of natural and edible encapsulation systems is a challenge for the food industry. This study explored two kinds of nanoparticles (NPs) made by zein and gum arabic (GA) and investigated the protective and controlled release effect of the formed NPs on rutin. Single‐layer NPs (ZG) formed with a zein and GA mixture and double‐layer NPs (ZWG) with one inner layer of zein and one outer layer of GA were prepared with a series of mass ratios of zein to GA. The particle size, polydispersity index, and zeta potential were obtained, and the structure and morphology of the NPs were observed using scanning electron microscopy. As shown by the differential scanning calorimeter and thermogravimetric analysis, the heat resistance of ZG is higher than the heat resistance of ZWG. ZG showed slower release of rutin in the simulated gastric and small intestinal solutions than ZWG. These results will help in understanding the different behaviors of protection and controlled release of layered NPs made by mixtures of biopolymers, which can be directly applied to the design of delivery systems of sensitive bioactive compounds in the food industry.